Consensus statement on standards for neurocritical care units in low-income and middle-income countries (LMICs) - Gentle S., Shrestha; Hemanshu, Prabhakar; Charu, Mahajan; Indu, Kapoor; Sarah L., Livesay; Venkatkrishna, Rajajee; Kapil, Zirpe; Walter, Videtta; Susmita Gisele, Sampaio Silva; Samuel Ern Hung, Tsan (Elsevier Inc., 2026)
The disease burden of severe neurological and neurosurgical illnesses in low-income and middle-income countries (LMICs) is high. Management of these patients by a dedicated neurocritical care team can improve outcome. Globally, there is significant variation in organization, structure, and outcome of patients with neurocritical illnesses. This consensus statement aims to contextualize the standards for neurological critical care units (NCCUs) in LMICs. Recommendations were made about organization and infrastructure, personnel, logistics, training, education, and process for developing neurocritical care program appropriate for LMICs. Methods: The steering committee for the consensus statement was formed under the leadership of Society of Neurocritical Care (SNCC), India. With permission from Neurocritical Care Society (NCS) and the NCS guidelines committee, the previously published standards for NCCUs by NCS was used for a web-based survey. The Delphi method was used to gather consensus. A total of 28 experts from 21 nations, all from LMICs, participated in the Delphi. Responses were formally collated, reviewed, and incorporated into the final document. For Level 1 NCCUs, we found that LMIC experts have recommended few parameters that were considered optional by NCS. However, for Level 2 and 3 ICUs, many recommendations from NCS were suggested to be considered as optional by LMIC experts. We have made attempts to explain the variation in recommendations. The recommendations should be tested for feasibility at the local settings before implementing them.